Fatwa DSN-MUI Tentang Online Shop Syariah Perspektif Maqashid Syariah: (Analisis Maqashid Syariah Pendekatan Sistem Jasser Audah) - Syafiq Sugeng Riyadi (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Information and communication technology advancements have significantly impacted various aspects of life, including the economy. One important innovation that has emerged is online shopping, which has become a primary trade channel. This study analyzes the DSN-MUI fatwa on Sharia online shops using Jasser Auda's maqashid syariah system approach. A qualitative research methodology was utilized to assess the fatwa's efficacy and applicability. The analysis shows how DSN-MUI Fatwa No.146/DSN-MUI/XII/2021 applies the principles of maqashid sharia, such as the cognitive nature emphasizing deep understanding in transactions, and the interrelatedness of legal elements ensuring the responsibility of sellers and delivery service providers. The wholeness of the legal system is maintained by viewing the entire transaction process as a single unit. Openness to technology is reflected in the recognition of online shopping platforms and various payment methods. The fatwa's multi-dimensionality covers social, practical, economic, and ethical dimensions. The fatwa's purposefulness is evident in efforts to ensure fair and beneficial transactions, emphasizing transparency, the right of choice (khiyar), and dispute resolution mechanisms.